2022
DOI: 10.7759/cureus.31768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isolated Calcaneal Spur Excision and Plantar Fasciotomy in Addition to Spur Excision in Patients With Plantar Heel Pain Accompanied by Calcaneal Spur

Abstract: Introduction:The aim of this study is to clinically compare isolated calcaneal spur excision and plantar fascia release in addition to spur excision in patients with plantar heel pain accompanied by a calcaneal spur.Method: Patients who did not benefit from conservative treatment and underwent surgical excision of the calcaneal spur and/or plantar fasciotomy were retrospectively evaluated. The patients were divided into two groups according to the surgical procedure performed. The evaluation was done according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Several studies have found that endoscopic plantar fascia release is often satisfactory in the treatment of recalcitrant plantar fasciitis. 10 , 26 , 27 Cottom et al 28 found that AOFAS scores and VAS scores of patients with recalcitrant plantar fasciitis improved significantly during a 5‐year follow‐up period after inflammatory tissue debridement of the plantar fascia. Rizk et al 29 found that heel drilling and decompression combined with metatarsal fascia laxation was effective in the treatment of recalcitrant plantar fasciitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that endoscopic plantar fascia release is often satisfactory in the treatment of recalcitrant plantar fasciitis. 10 , 26 , 27 Cottom et al 28 found that AOFAS scores and VAS scores of patients with recalcitrant plantar fasciitis improved significantly during a 5‐year follow‐up period after inflammatory tissue debridement of the plantar fascia. Rizk et al 29 found that heel drilling and decompression combined with metatarsal fascia laxation was effective in the treatment of recalcitrant plantar fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery plays an important role in patients with plantar fasciitis and bone spurs that fail conservative treatment, 7,8 such as metatarsal fascia lysis, calcaneal spur grinding, calcaneal drilling decompression, gastrocnemius release, and so on. 4,[9][10][11] Because bone spurs increase the risk of heel pain, 12 most surgeons remove them as they appear. However, few studies have proposed surgical protocols for plantar fasciitis with bone spurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical intervention for heel spurs is generally considered a last resort when all other treatment options have failed, and symptoms persist. The surgical objective is to remove the bony protrusion and address any accompanying soft tissue damage ( 23 ). The choice of surgical technique may vary depending on the condition's severity and the individual's unique circumstances.…”
Section: Surgical Interventionmentioning
confidence: 99%
“…However, regarding the calcaneal spur formations that may first come to mind in the etiology of patients with plantar fasciitis, the results are contradictory regarding the relationship between the size of the spurs and pain and symptoms [13,14]. For this reason, different treatments for many other mechanisms, including spur excision, can be used to treat the disease [15,16]. In this study, the mean age of the patients was 41, which is consistent with the age range often observed in similar studies.…”
mentioning
confidence: 99%